Developing brains and changing worlds: Macroenvironmental changes and their association with brain development - Juan F. Quinones; Tobias Banaschewski; Arun L.W. Bokde; Sylvane Desrivières; Herta Flor; Hugh Garavan; Penny Gowland; Antoine Grigis; Andreas Heinz; Herve Lemaitre; Jean-Luc Martinot; Marie-Laure Paillère Martinot; et al. (Environmental Research, 2026)

Anatomical connectivity development constrains medial–lateral topography in the dorsal prefrontal cortex - Wen Li; Weiyang Shi; Haiyan Wang; Jin Li; Congying Chu; Yu Zhang; Yue Cui; Luqi Cheng; Kaixin Li; Yuheng Lu; Liang Ma; Ming Song; et al. (Science Bulletin, 2026)

Distinct neural networks of emotional valence and uncertainty in the human amygdala underlying different mental disorders - Shitong Xiang; Chao Xie; Xiao Xiao; Tobias Banaschewski; Gareth J. Barker; Arun L.W. Bokde; Herta Flor; Antoine Grigis; Hugh Garavan; Penny Gowland; Andreas Heinz; Rüdiger Brühl; et al. (Science Bulletin, 2025)

Light Cannabis Use and the Adolescent Brain: An 8-years Longitudinal Assessment of Mental Health, Cognition, and Reward Processing - Inês Macedo; Tiago O. Paiva; Rita Pasion; Laura Daedelow; Andreas Heinz; Ana Magalhães; Tobias Banaschewski; Arun L. W. Bokde; Sylvane Desrivières; Herta Flor; Antoine Grigis; Hugh Garavan; et al. (Psychopharmacology, 2024)
Rationale For decades, cannabis has been the most widely used illicit substance in the world, particularly among youth. Research suggests that mental health problems associated with cannabis use may result from its effect on reward brain circuit, emotional processes, and cognition. However, findings are mostly derived from correlational studies and inconsistent, particularly in adolescents. Objectives and Methods Using data from the IMAGEN study, participants (non-users, persistent users, abstinent users) were classified according to their cannabis use at 19 and 22 years-old. All participants were cannabis-naïve at baseline (14 years-old). Psychopathological symptoms, cognitive performance, and brain activity while performing a Monetary Incentive Delay task were used as predictors of substance use and to analyze group differences over time. Results Higher scores on conduct problems and lower on peer problems at 14 years-old ( n = 318) predicted a greater likelihood of transitioning to cannabis use within 5 years. At 19 years of age, individuals who consistently engaged in low-frequency (i.e., light) cannabis use ( n = 57) exhibited greater conduct problems and hyperactivity/inattention symptoms compared to non-users ( n = 52) but did not differ in emotional symptoms, cognitive functioning, or brain activity during the MID task. At 22 years, those who used cannabis at both 19 and 22 years-old n = 17), but not individuals that had been abstinent for ≥ 1 month ( n = 19), reported higher conduct problems than non-users ( n = 17). Conclusions Impairments in reward-related brain activity and cognitive functioning do not appear to precede or succeed cannabis use (i.e., weekly, or monthly use). Cannabis-naïve adolescents with conduct problems and more socially engaged with their peers may be at a greater risk for lighter yet persistent cannabis use in the future.

Whole-brain gray matter maturation trajectories associated with autistic traits from adolescence to early adulthood - Guillaume Gros; Ruben Miranda Marcos; Anthony Latrille; Ana Saitovitch; Fanny Gollier-Briant; Philippe Fossati; Liane Schmidt; Tobias Banaschewski; Gareth J. Barker; Arun L. W. Bokde; Sylvane Desrivières; Antoine Grigis; et al. (Brain Structure and Function, 2023)
A growing number of evidence supports a continued distribution of autistic traits in the general population. However, brain maturation trajectories of autistic traits as well as the influence of sex on these trajectories remain largely unknown. We investigated the association of autistic traits in the general population, with longitudinal gray matter (GM) maturation trajectories during the critical period of adolescence. We assessed 709 community-based adolescents (54.7% women) at age 14 and 22. After testing the effect of sex, we used whole-brain voxel-based morphometry to measure longitudinal GM volumes changes associated with autistic traits measured by the Social Responsiveness Scale (SRS) total and sub-scores. In women, we observed that the SRS was associated with slower GM volume decrease globally and in the left parahippocampus and middle temporal gyrus. The social communication sub-score correlated with slower GM volume decrease in the left parahippocampal, superior temporal gyrus, and pallidum; and the social cognition sub-score correlated with slower GM volume decrease in the left middle temporal gyrus, the right ventromedial prefrontal and orbitofrontal cortex. No longitudinal association was found in men. Autistic traits in young women were found to be associated with specific brain trajectories in regions of the social brain and the reward circuit known to be involved in Autism Spectrum Disorder. These findings support both the hypothesis of an earlier GM maturation associated with autistic traits in adolescence and of protective mechanisms in women. They advocate for further studies on brain trajectories associated with autistic traits in women.

Temporo-basal sulcal connections: a manual annotation protocol and an investigation of sexual dimorphism and heritability - Kevin de Matos; Claire Cury; Lydia Chougar; Lachlan T. Strike; Thibault Rolland; Maximilien Riche; Lisa Hemforth; Alexandre Martin; Tobias Banaschewski; Arun L. W. Bokde; Sylvane Desrivières; Herta Flor; et al. (Brain Structure and Function, 2023)

Federated Analysis in COINSTAC Reveals Functional Network Connectivity and Spectral Links to Smoking and Alcohol Consumption in Nearly 2,000 Adolescent Brains - Harshvardhan Gazula; Kelly Rootes-Murdy; Bharath Holla; Sunitha Basodi; Zuo Zhang; Eric Verner; Ross Kelly; Pratima Murthy; Amit Chakrabarti; Debasish Basu; Subodh Bhagyalakshmi Nanjayya; Rajkumar Lenin Singh; et al. (Neuroinformatics, 2023)

Longitudinal associations between amygdala reactivity and cannabis use in a large sample of adolescents - Philip A. Spechler; Bader Chaarani; Catherine Orr; Matthew D. Albaugh; Nicholas R. Fontaine; Stephen T. Higgins; Tobias Banaschewski; Arun L. W. Bokde; Erin Burke Quinlan; Sylvane Desrivières; Herta Flor; Antoine Grigis; et al. (Psychopharmacology, 2020)

Volumetric brain correlates of approach-avoidance behavior and their relation to chronic back pain - Frauke Nees; Michaela Ruttorf; Xaver Fuchs; Mariela Rance; Nicole Beyer (Brain Imaging and Behavior, 2020)

Memory-guided attention: bilateral hippocampal volume positively predicts implicit contextual learning - Mario A. Rosero; Tobias Winkelmann; Sebastian Pohlack; Juliana Cavalli; Frauke Nees; Herta Flor (Brain Structure and Function, 2019)

Neural correlates of reappraisal considering working memory capacity and cognitive flexibility - Jenny Zaehringer; Rosalux Falquez; Anna-Lena Schubert; Frauke Nees; Sven Barnow (Brain Imaging and Behavior, 2018)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Structural brain correlates of heart rate variability in a healthy young adult population - Tobias Winkelmann; Julian F. Thayer; Sebastian Pohlack; Frauke Nees; Oliver Grimm; Herta Flor (Brain Structure and Function, 2017)

Brain morphology correlates of interindividual differences in conditioned fear acquisition and extinction learning - Tobias Winkelmann; Oliver Grimm; Sebastian T. Pohlack; Frauke Nees; Raffaele Cacciaglia; Ramona Dinu-Biringer; Frauke Steiger; Manon Wicking; Michaela Ruttorf; Lothar R. Schad; Herta Flor (Brain Structure and Function, 2016)

Oppositional COMT Val158Met effects on resting state functional connectivity in adolescents and adults - Bernhard M. Meyer; Julia Huemer; Ulrich Rabl; Roland N. Boubela; Klaudius Kalcher; Andreas Berger; Tobias Banaschewski; Gareth Barker; Arun Bokde; Christian Büchel; Patricia Conrod; Sylvane Desrivières; et al. (Brain Structure and Function, 2016)

Dissociable roles for hippocampal and amygdalar volume in human fear conditioning - Raffaele Cacciaglia; Sebastian T. Pohlack; Herta Flor; Frauke Nees (Brain Structure and Function, 2015)

A target sample of adolescents and reward processing: same neural and behavioral correlates engaged in common paradigms? - Frauke Nees; Sabine Vollstädt-Klein; Mira Fauth-Bühler; Sabina Steiner; Karl Mann; Luise Poustka; Tobias Banaschewski; Christian Büchel; Patricia J. Conrod; Hugh Garavan; Andreas Heinz; Bernd Ittermann; et al. (Experimental Brain Research, 2012)

Inhibition of cortisol production by metyrapone enhances trace, but not delay, eyeblink conditioning - Frauke Nees; Steffen Richter; Johanna Lass-Hennemann; Terry D. Blumenthal; Hartmut Schächinger (Psychopharmacology, 2008)

Inhibition of cortisol production by metyrapone enhances trace, but not delay, eyeblink conditioning - Frauke Nees; Steffen Richter; Johanna Lass-Hennemann; Terry D. Blumenthal; Hartmut Schächinger (Psychopharmacology, 2008)